Hormonal Contraception in Men - Walton, M.; Anderson, R. A. (Current Drug Targets - Immune, Endocrine & Metabolic Disorders, 2005)
All major advances in the development of hormonal methods of contraception over the past 40 years have been exclusively female orientated with male hormonal contraception forever
Keywords: testosterone